Influence of surface cracks on Hertzian fracture - Warren, P; Hills, D; Roberts, S (Inst of Physics Publ Ltd, 1994)
The Hertzian indentation test is an alternative to the more familiar Vickers indentation test for the evaluation of the fracture properties of brittle materials. The distinct advantage of the Hertzian test is that the deformation produced by the indenter is entirely elastic until fracture occurs. Calculation of the stress intensity factors for cracks driven by the Hertzian field is complex because of the rapid decay of this field with depth. The results of recent calculations of stress intensity factors for surface-breaking cracks driven by this field are presented. The effects of crack shape (plane, semicircular or semielliptical) on the stress intensity factors are also considered. Finally, the use of Hertzian indentation testing for evaluating surface flaw densities is critically evaluated, and a computational method for determining such densities (which take into account the steep stress gradients) from a knowledge of just the fracture loads (obtained from a series of tests) is described.